Peningkatan Keterampilan Membaca dan Menulis Arab Pegon Santri TPQ Nu Ar Rohman - Mazidatul Faizah; Siti Hanifah; Tomi Ariffaturakhman (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2021)
The community service activity is TPQ NU Ar Rohman Karangturi Hamlet, Karangdagang Village. The learning process at TPQ is still focused only on teaching reading the Qur'an. There has been no learning about writing and reading using the Arabic script Pegon, so we need to learn about it. The approach method used includes lecture, discussion, and expository methods. The preparation of the material was then carried out by evaluating and compiling a long-term plan. The results obtained by partner coordination went well, the material preparation was good, and the implementation of the learning assessment program for TPQ NU-Arrahman students showed that 70% of the participants had good skills in writing pegon Arabic. As many as 30% of participants were in the category with fairly good skills which was influenced by the age of the student teacher around 5-7 years. In addition, it also produces the publication of the Arabic Pegon study book.